Pengaruh Teknologi Informasi dan Pemahaman Sistem Informasi Akuntansi terhadap Kinerja Pengelolaan Keuangan Pemerintah - Marwah Yusuf (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
This study aims to examine and analyze the effect of Information Technology and Information Systems Understanding on Government Financial Management's Performance at Regional Work Units in Makassar City Government. The sampling technique used the purposive sampling method by determining specific criteria so that the number of samples was 75 respondents representing three respondents from 25 OPDs in Makassar City. Data was collected through the results of a questionnaire distributed to respondents. The data collected was tested using instrument tests (validity and reliability tests), classical assumption tests (normality tests and heteroscedasticity tests), and analyzed using descriptive analysis methods and inferential analysis. The research hypothesis testing was carried out by (partial test, F statistical test, and determination coefficient test.) This study found a positive and significant effect between Information Technology, Understanding Accounting Information Systems, and Information Technology and Understanding Accounting Information Systems simultaneously positive and significant effects on Government Financial Managers' Performance